Risk Factors Analysis in Various Subtypes of Ischemic Stroke According to TOAST Criteria in a Tertiary Care Hospital (Bangladesh Journal of Neuroscience, 2019)
Background: Stroke is the third leading cause of death in adult population throughout the world and is the most common cause of severe adult physical disability. The aim of the study is to identify the major risk factors in various subtypes of ischemic stroke according to TOAST criteria. Methods: A Cross-sectional observational study was conducted from January, 2018 to December 2018 in the department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. All the patients of first ever ischemic stroke within 14 days diagnosed by history, clinical examination and neuroimaging (CT scan of head / MRI of brain), meeting the inclusion and exclusion criteria were included in the study. Results: Present study showed that among the 52 ischemic stroke patients mean age of the respondents was 57 ± 12.37 years with a slightly higher male predominance. Male to female ratio was 1.2:1. Dyslipidemia 44 (84.6 %) and hypertension 37 (71.2 %) were the most common risk factors, followed by obesity and overweight 33(63.5%), smoking 32 (61.5%), diabetes mellitus 29 (55.8%), family history of vascular event 27(51.9 %) and past history of vascular event 14 (26.9%). TOAST Subtype distribution of study population was large-artery atherosclerosis 18 (34.6%) followed by cardioembolism 11(21.2%), small-vessel occlusion 10(19.2%), stroke of other determined etiology 3(5.8%), and stroke of undetermined etiology 10(19.2 %) of patients. In cardioembolic subtype significant association was found with ischemic heart disease (P=0.001) and chronic rheumatic heart disease (P=